UNDERPRESCRIPTION OF SGLT2i IN TYPE 2 DIABETES PATIENTS WITH CARDIORENAL DISEASE IN A PUBLICLY FUNDED TERTIARY CENTER IN MALAYSIA - Luk, Kuok Jie; Ho, Tze Hau; Muagan, Sugenthiran; Kahar, Nazri Ab; Chiew, Ken Seng (Journal of the ASEAN Federation of Endocrine Societies, 2024)
INTRODUCTION/BACKGROUND Large-scale randomized controlled trials have proven that sodium-glucose cotransporter-2 inhibitors (SGLT2i) significantly reduce risks of atherosclerotic cardiovascular disease (ASCVD), heart failure (HF) and chronic kidney disease (CKD) in patients with type 2 diabetes (T2D). However, TARGET-T2D has shown that the use of guidelinedirected medical therapy with SGLT2i is suboptimal even in Greater Kuala Lumpur, which has the highest mean household incomes in Malaysia. METHODOLOGY We hypothesize that the use is even lower in our centre. This cross-sectional clinical audit involves all patients aged 18 years and older with T2D who visited the general medicine clinic of Hospital Sultan Ismail from 31st March to 4th April 2024. Their electronic medical records were reviewed for the presence of ASCVD, HF and CKD, and SGLT2i prescriptions. RESULTS A total of 224 patients were included. After excluding those with eGFR <20 ml/min/1.73 m2 , 175 patients were identified. Among them, 116 (66.3%) have at least one cardiorenal disease. Fifty patients (28.6%) have ASCVD, 31 (17.7%) have HF and 92 (52.3%) have CKD. However, only 29 (25%) are on SGLT2i. Interestingly, it was higher than the 13.2% reported by TARGET-T2D for general medicine clinics in Greater Kuala Lumpur. Aside from 3 patients who received hospital-funded SGLT2i, most (89.7%) are self-funded. Among the 87 patients with indications to start SGLT2i but are not on it, six were recommended to purchase the medication but could not afford it. The other 81 patients did not receive such advice. None had SGLT2i withheld due to urogenital tract infections or euglycemic diabetic ketoacidosis. CONCLUSION SGLT2i remains critically underused in T2D patients with cardiorenal disease. Increasing public funding for SGLT2i could help bridge the gap between evidence and clinical practice. Even if public funding is not sufficient, health professionals should advise patients with indications to start SGLT2i to self-purchase, considering its overwhelming clinical benefits.